Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of 2018
DOI: 10.1145/3236024.3264840
|View full text |Cite
|
Sign up to set email alerts
|

Towards counterexample-guided k-induction for fast bug detection

Abstract: Recently, the k-induction algorithm has proven to be a successful approach for both finding bugs and proving correctness. However, since the algorithm is an incremental approach, it might waste resources trying to prove incorrect programs. In this paper, we propose to extend the k-induction algorithm in order to shorten the number of steps required to find a property violation. We convert the algorithm into a meet-in-the-middle bidirectional search algorithm, using the counterexample produced from over-approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Results over the SV-COMP 2018 benchmark suite show that ESBMC is the strongest k-induction tool currently available. We are currently extending the k-induction proof rule to use information from the inductive step, to make bug finding more efficiently [16].…”
Section: ) Setupmentioning
confidence: 99%
“…Results over the SV-COMP 2018 benchmark suite show that ESBMC is the strongest k-induction tool currently available. We are currently extending the k-induction proof rule to use information from the inductive step, to make bug finding more efficiently [16].…”
Section: ) Setupmentioning
confidence: 99%
“…In practice, the bkind algorithm performs a bidirectional search for bugs in the program state space to quickly refute properties. Given the current knowledge in software model checking, our extension has not previously been described or evaluated in the literature, but we have already provided preliminary results of this approach on a limited number of small benchmarks [11]. Similar techniques do exist, however, in other domains: Bischoff et al [12] describe a technique called "target enlargement" which combines binary decisions diagrams (BDDs) and Boolean Satisfiability (SAT) solvers to reduce the time to find property violations in hardware verification, and Bradley et al introduced "property-directed reachability" (or IC3) procedure for safety verification of systems [13] and have shown that IC3 can scale on certain benchmarks, where k-induction fails to succeed.…”
Section: Introductionmentioning
confidence: 99%